Serum antibodies to Pseudomonas aeruginosa in cystic fibrosis. Issue 11 (November 1986) - Brett, M M; Ghoneim, A T; Littlewood, J M
Abstract : Serum IgG antibodies to Pseudomonas aeruginosa cell surface antigens were determined by enzyme linked immunosorbent assay. Titres in patients without cystic fibrosis were low (140-235). Those in patients with cystic fibrosis who were chronically infected by P. aeruginosa were very high (1100-20, 500), while patients who grew the organism intermittently had lower titres (160-4400). Longitudinal studies showed that raised titres were observed at a very early stage of infection. High titres were associated with a poor clinical state, while low titres were associated with a better clinical state in both chronic and intermittently infected patients with cystic fibrosis. These results suggest that this test is a specific and sensitive measure of the severity and progress of the different stages of pulmonary infection by P. aeruginosa in patients with cystic fibrosis.